The Drosophila easily shocked gene: A mutation in a phospholipid synthetic pathway causes seizure, neuronal failure, and paralysis. - Pavlidis, P.; Ramaswami, M.; Tanouye, M.A. (Cell, 1994)
We have characterized easily shocked (eas), a Drosophila "band-sensitive" paralytic mutant. Electrophysiological recordings from flight muscles in the giant fiber pathway of adult eas flies reveal that induction of paralysis with electrical stimulation results in a brief seizure, followed by a failure of the muscles to respond to giant fiber stimulation. Molecular cloning, germline transformation, and biochemical experiments show that eas mutants are defective in the gene for ethanolamine kinase, which is required for a pathway of phosphatidylethanolamine synthesis. Assays of phospholipid composition reveal that total phosphatidylethanolamine is decreased in eas mutants. The data suggest that eas bang sensitivity is due to an excitability defect caused by altered membrane phospholipid composition.